Sedimentary environment and palaeogeography of the ?Palaeocene-Middle Eocene Kashkan Formation, Zagros fold-thrust belt, SW Iran - Yeganeh, Bizhan; Feiznia, Sadat; van Loon, A.J. (Tom) (Geologos, 2012)
The Kashkan Formation (?Palaeocene to Middle Eocene) in the Zagros fold-thrust belt, SW Iran, which is intercalated between to marine limestone formations, consists of conglomerates, sandstones and siltstones. The sedimentology and the palaeogeography of the Kashkan Formation had not received any attention thus far, but have now been studied in seven sections, situated in the province of Lorestan. The sediments form twelve lithofacies, three ichnosubfacies and seven architectural elements, which are described, depicted and analysed. The analysis leads to the conclusion that most sediments accumulated in a low-sinuosity, low-gradient braided-river system (characterised by mainly unidirectional palaeocurrent directions, and by sheetfloods), that occasionally showed meandering characteristics (represented by overbank deposits and large bars). The deposits of this system closely resemble those of the South Saskatchewan River in Canada, which is considered as the classical example of a sand-bed braided river. The river flowed roughly from North to South, as deduced by palaeocurrent indicators such as imbrication and large-to medium-scale trough cross-stratification (direction measured in the trough axes). This current direction is supported by the southward to south-westward thinning of the formation and by the diminishing average grain size in the same direction. The trace fossils in the Kashban Formation fit all in the Skoyenia ichnofacies, which has here three ichnosubfacies which allow a more detailed palaeoenvironmental reconstruction, indicating that the braided stream passed into the low-energy shoreface zone of a tidally-influenced sea.